Surface-treated copper foil and copper foil substrate
Patent Information
- Application Number
- CN202110888384.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-19
- Filing Date
- 2021-08-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-08-03
AI Technical Summary
[0004]有鉴于此,本发明提供有一种改良的表面处理铜箔及铜箔基板,以解决现有技术中所存在的缺陷
[0007]根据本发明的实施例,通过将处理面的极点高度(Sxp)控制为0.4~2.5μm,且通过将磁滞回线在磁场为零时的第一磁化强度和第二磁化强度之间的绝对差值控制在特定区间,例如为20~1200emu/m3,可改善铜箔基板的信号传递损失以及附着性。
Smart Images

Figure CN115643675B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of copper foil technology, and more particularly to a surface-treated copper foil and its copper foil substrate. Background Technology
[0002] As electronic products become increasingly thinner and lighter, and more capable of transmitting high-frequency signals, the demand for copper foil and copper foil substrates is also rising. Generally, the copper conductive lines of a copper foil substrate are carried by an insulating substrate, and through the layout design of the conductive lines, electrical signals can be transmitted to a predetermined area along a predetermined path. Furthermore, for copper foil substrates used to transmit high-frequency electrical signals (e.g., above 10 GHz), the conductive lines of the copper foil substrate must be further optimized to reduce signal transmission loss caused by the skin effect. The skin effect refers to the phenomenon that as the frequency of an electrical signal increases, the current transmission path becomes increasingly concentrated on the surface of the conductor, such as the surface of the conductor immediately adjacent to the substrate. To reduce signal transmission loss caused by the skin effect, current methods aim to flatten the surface of the conductors immediately adjacent to the substrate in the copper foil substrate as much as possible. However, even though the above methods can indeed reduce the signal transmission loss generated by the copper foil substrate, there are still technical shortcomings that need to be overcome.
[0003] Therefore, it is still necessary to provide a surface-treated copper foil and a copper foil substrate to address the deficiencies in the prior art. Summary of the Invention
[0004] In view of this, the present invention provides an improved surface-treated copper foil and copper foil substrate to overcome the defects existing in the prior art.
[0005] According to an embodiment of the present invention, a surface-treated copper foil is provided, comprising a treated surface with a pole height (Sxp) of 0.4–2.5 μm. The hysteresis loop of the surface-treated copper foil exhibits a first magnetization and a second magnetization when the magnetic field is zero, wherein the absolute difference between the first and second magnetizations is 20–1200 emu / m. 3 .
[0006] According to another embodiment of the present invention, a copper foil substrate is provided. The copper foil substrate includes a carrier plate and the surface-treated copper foil described above, wherein the treated surface of the surface-treated copper foil is attached to the carrier plate.
[0007] According to an embodiment of the present invention, the pole height (Sxp) of the processed surface is controlled to be 0.4 to 2.5 μm, and the absolute difference between the first magnetization and the second magnetization of the hysteresis loop when the magnetic field is zero is controlled within a specific range, for example, 20 to 1200 emu / m.3 It can improve signal transmission loss and adhesion of copper foil substrates. Attached Figure Description
[0008] To facilitate understanding of the following text, reference should be made to the accompanying drawings and detailed textual descriptions while reading this invention. Specific embodiments of the invention are explained in detail through reference to the corresponding drawings, which also illustrate the working principles of these embodiments. Furthermore, for clarity, features in the drawings may not be drawn to scale; therefore, the dimensions of some features in certain drawings may be intentionally enlarged or reduced. Figure 1 This is a schematic diagram showing the relationship between the pole height (Sxp) and loading rate (mr) of a surface-treated copper foil according to an embodiment of the present invention. Figure 2 This is a cross-sectional schematic diagram of a surface-treated copper foil according to an embodiment of the present invention. Figure 3 This is a schematic diagram of a stripline according to an embodiment of the present invention.
[0009] The reference numerals in the attached figures are explained as follows: 100… Electrolytic copper foil 100A…processing surface 110… Copper foil body 110A…First page 110B…Second side 112a…First surface treatment layer 112b…Second surface treatment layer 114… Coarsening layer 116a…First passivation layer 116b…Second passivation layer 118a…First anti-rust layer 118b…Second anti-rust layer 120…coupling layer 300…band 302… wire 304…dielectric 306-1…Grounding electrode 306-2…Grounding electrode h…thickness H1…height H2…height M1…load rate M2…load rate P1…First data point P2…Second data point t…thickness w…width Detailed Implementation
[0010] Specific embodiments of surface-treated copper foil and copper foil substrates are described below to enable those skilled in the art to implement the present invention. These specific embodiments are illustrated with corresponding drawings, which form part of the embodiments. Although embodiments of the present invention are disclosed below, they are not intended to limit the invention. Any modifications and refinements can be made by those skilled in the art without departing from the spirit and scope of the invention. Unless otherwise specified, the methods used in the embodiments and experimental examples are conventional methods.
[0011] Regarding the spatial-related descriptive terms mentioned in this invention, the meanings of terms such as "on" and "above" should be interpreted in the broadest sense, such that "on" and "above" not only refer to being directly on something, but also include being on something when there is an intermediate feature or intermediate layer between them. Furthermore, "on" or "above" not only refer to being above or above something, but also include being above or above something (i.e., directly on) when there is no intermediate feature or intermediate layer between them.
[0012] Although the present invention uses terms such as first, second, third, etc., to describe various elements, components, regions, layers, and / or blocks, it should be understood that such elements, components, regions, layers, and / or blocks should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer, and / or block from another, and do not in themselves imply or represent any prior ordinal number of the element, nor do they represent the arrangement order of one element with another, or the order of manufacturing methods. Therefore, without departing from the scope of the specific embodiments of the present invention, the first element, component, region, layer, or block discussed below may also be referred to as a second element, component, region, layer, or block.
[0013] Furthermore, unless otherwise indicated below, the numerical parameters set forth in this invention and the claims are approximate numbers, which may vary as needed, or should at least be interpreted according to the meaningful number of digits of the invention and using the usual carry method. In this invention, a range may be expressed as from one endpoint to another, or between two endpoints. Unless otherwise stated, all ranges in this invention include endpoints.
[0014] It should be understood that, without departing from the spirit of the present invention, the technical features in the different embodiments described below can be substituted, recombined, or mixed with each other to form other embodiments.
[0015] The surface-treated copper foil described herein includes a treated surface. The copper foil body of the surface-treated copper foil can be formed by an electrodeposition (or electrolysis, electrolytic deposition, electroplating) process, and it can have two oppositely arranged drumsides and a deposited side.
[0016] Optionally, a surface treatment layer may be respectively disposed on at least one of the roller surface and the deposition surface of the copper foil body. The surface treatment layer may be a single-layer structure or a multi-layer stacked structure. For example, the surface treatment layer may be a multi-layer stacked structure comprising multiple sub-layers, and each surface treatment layer may be disposed on the roller surface and the deposition surface of the copper foil body respectively, but is not limited thereto. The sub-layers in each surface treatment layer may be selected from the group consisting of roughening layers, passivation layers, rust-preventing layers, and coupling layers, but is not limited thereto.
[0017] According to embodiments of the present invention, a surface-treated copper foil is provided, which can be laminated to a carrier plate to form a copper foil substrate. According to embodiments of the present invention, since the treated surface of the surface-treated copper foil is laminated to the carrier plate in a subsequent process, the peak extreme height (Sxp) of the treated surface affects the adhesion between the surface-treated copper foil and the polymer carrier plate. According to embodiments of the present invention, the peak extreme height (Sxp) of the treated surface can be 0.4–2.5 μm, for example, 0.4–2.2 μm, 0.4–2.0 μm, or 0.4–1.8 μm. The peak extreme height (Sxp) is defined according to ISO 25178-2:2012, and its measurement results can be exemplified as follows: Figure 1 As shown.
[0018] Figure 1 This is a schematic diagram illustrating the relationship between the pole height (Sxp) and material ratio (mr) of the surface-treated copper foil according to an embodiment of the present invention. The pole height (Sxp) can be the absolute difference between the corresponding height H1 of the first data point P1 and the corresponding height H2 of the second data point P2. According to the definition in ISO 25178-2:2012, the corresponding material ratio M1 of the first data point P1 is 2.5%, while the corresponding material ratio M2 of the second data point P1 is 50%. Since the pole height (Sxp) excludes high peaks with a material ratio below 2.5%, the influence of a few high peaks on roughness can be eliminated. A higher pole height (Sxp) is beneficial for increasing the adhesion between the surface-treated copper foil and the carrier (e.g., it is beneficial for increasing normal peel strength or infrared reflow peel strength), but when it is too high, it may exacerbate signal loss.
[0019] Furthermore, some layers in the surface-treated copper foil of this embodiment of the invention can be obtained by electrodeposition. For example, a copper foil body, a roughening layer, a passivation layer, and / or a rust-preventive layer can be formed by electrodeposition. During the electrodeposition process, the electrolyte may contain small amounts of ferromagnetic metal ions, such as iron ions, nickel ions, cobalt ions, or other metal ions, in addition to copper ions. These metal ions may originate from salts used as additives. Salts can be used to adjust the surface characteristics or roughness of each electrodeposited layer, or to adjust the crystallization characteristics or mechanical strength of each electrodeposited layer, but are not limited thereto. Therefore, when a copper foil body and some layers in the surface-treated layer (e.g., roughening layer, passivation layer, and / or rust-preventive layer) are formed by electrodeposition, these layers may contain small amounts of ferromagnetic metal. Since the magnetic susceptibility of ferromagnetic metal is 10... 1 ~10 6 Furthermore, it will be affected by the external magnetic field and generate residual magnetism, which will make the signal transmission loss more significant for conductors using the above-mentioned surface-treated copper foil as high-frequency signals.
[0020] Specifically, regarding the hysteresis loop generated by an applied magnetic field on a surface-treated copper foil, when the applied magnetic field is zero, the corresponding magnetization in the hysteresis loop can be a first magnetization and a second magnetization, respectively. According to an embodiment of the present invention, the value of the first magnetization of the hysteresis loop is greater than the value of the second magnetization, and both the first and second magnetization values can be positive, or the first magnetization can be positive and the second magnetization can be negative. According to an embodiment of the present invention, for a hysteresis loop that has reached magnetic saturation, the absolute difference between the first and second magnetization values is 20–1200 emu / m. 3 For example, 20-1000 emu / m 3 20~800emu / m 3 20~600emu / m 3 or 20-500 emu / m 3 .
[0021] According to an embodiment of the present invention, when the pole height (Sxp) of the processed surface is 0.4 to 2.5 μm, and the absolute difference between the first magnetization and the second magnetization is 20 to 1200 emu / m 3 At the same time, for the corresponding copper foil substrate and printed circuit board, the surface-treated copper foil and the polymer substrate in contact can simultaneously meet the requirements of low signal transmission loss, high normal peel strength, and high infrared reflow peel strength.
[0022] According to an embodiment of the present invention, when the pole height (Sxp) of the processed surface is further controlled to be 0.4 to 1.8 μm, and the absolute difference between the first magnetization and the second magnetization is 20 to 800 emu / m 3 This can further reduce the degree of signal transmission loss.
[0023] According to an embodiment of the present invention, when the pole height (Sxp) of the processed surface is 0.4 to 2.5 μm, and the absolute difference between the first magnetization and the second magnetization is further controlled to be 20 to 500 emu / m. 3 This can also further reduce the degree of signal transmission loss.
[0024] Furthermore, in cases where the outer surface of the surface treatment layer is a surface-treated copper foil, the silicon content in the surface treatment layer also affects the normal peel strength and the infrared reflow peel strength. According to an embodiment of the present invention, when X-ray photoelectron spectroscopy (XPS) analysis is performed on the treated surface using Ni, Cu, Zn, Co, Cr, Si, C, N, O, P, and S as the target atoms for analysis, the Si concentration of the surface treatment layer can be controlled to be 2–15 at% (at% is the atomic percentage), for example, 2.5–11.5 at% or 2.5–8.0 at%.
[0025] According to an embodiment of the present invention, when the pole height (Sxp) of the processed surface is 0.4 to 2.5 μm, and the absolute difference between the first magnetization and the second magnetization is 20 to 1200 emu / m 3 Furthermore, when the Si concentration of the surface treatment layer is controlled to be 2–15 at%, a certain infrared reflow peel strength can be maintained for the corresponding copper foil substrate and printed circuit board, and the situation of board explosion during infrared reflow peel strength test can be avoided. In addition, when the Si concentration of the surface treatment layer is controlled to be 2.5–11.5 at%, or 2.5–8 at%, the peel strength after infrared reflow can be further maintained (that is, a high peel strength retention rate).
[0026] The structure of the surface-treated copper foil described above can be illustrated as follows: Figure 2 . Figure 2 This is a cross-sectional schematic diagram of a surface-treated copper foil according to an embodiment of the present invention. Figure 2As shown, the thickness of the surface-treated copper foil 100 is typically greater than or equal to 6 μm, for example, between 7 and 250 μm, or between 9 μm and 210 μm, or any value therein, such as 12 μm, 18 μm, 35 μm, 70 μm, 105 μm, 140 μm, 175 μm, or 210 μm. The above thicknesses are weight-average thicknesses, i.e., the weight per unit area (g / m²) of the surface-treated copper foil. 2 Divide by the density of copper foil (g / m³) 3 To obtain the weight-average thickness, where the inner layer at the surface of the surface-treated copper foil is extremely thin, the copper foil density can be adopted as the theoretical copper density of 8.96 (g / cm³). 3 The surface-treated copper foil 100 includes a treated surface 100A and at least a copper foil body 110. The copper content of the copper foil body 110 is greater than or equal to 99%. One of the deposition surface and the roller surface of the copper foil body 110 corresponds to the first surface 110A, and the other corresponds to the second surface 110B. According to an embodiment of the invention, the deposition surface corresponds to the first surface 110A, and the roller surface corresponds to the second surface 110B. According to an embodiment of the invention, although the copper foil body 110 is mainly composed of copper, it may still include small amounts of ferromagnetic metals, such as iron, nickel, and cobalt, thus causing the magnetization intensity of the hysteresis loop of the surface-treated copper foil to be affected by these ferromagnetic metals.
[0027] In addition to the copper foil body 110, the surface-treated copper foil 100 may optionally include a surface treatment layer, such as a first surface treatment layer 112a and a second surface treatment layer 112b, which are respectively disposed on the first surface 110A and the second surface 110B. The outer surface of the first surface treatment layer 112a can be regarded as the treated surface 100A of the surface-treated copper foil 100, and this treated surface 100A will contact the carrier plate through the subsequent process of pressing the surface-treated copper foil 100 onto the carrier plate.
[0028] The first surface treatment layer 112a and the second surface treatment layer 112b can each be a single-layer structure or a multi-layer stacked structure. In the case where the first surface treatment layer 112a is a multi-layer stacked structure including multiple sub-layers, each sub-layer can be selected from the group consisting of the roughening layer 114, the first passivation layer 116a, the first rust-preventing layer 118a, and the coupling layer 120; and in the case where the second surface treatment layer 112b is a multi-layer stacked structure including multiple sub-layers, each sub-layer can be selected from the group consisting of the second passivation layer 116b and the second rust-preventing layer 118b. The compositions of the first passivation layer 116a and the second passivation layer 116b can be the same or different from each other, and the compositions of the first rust-preventing layer 118a and the second rust-preventing layer 118b can be the same or different from each other.
[0029] The aforementioned roughening layer 114 includes roughening particles (nodules). These roughening particles can be used to improve the surface roughness of the copper foil body 110, and can be copper roughening particles or copper alloy roughening particles. Furthermore, to prevent the roughening particles from peeling off from the copper foil body, the roughening layer 114 may further include a capping layer disposed on the roughening particles, the capping layer covering the roughening particles. The pole height (Sxp) of the surface-treated copper foil 100 can be adjusted by adjusting the number and size of the roughening particles in the roughening layer. For example, for roughening particles and capping layers formed by electrolytic deposition, the number and size of the roughening particles can be adjusted by adjusting the type of additives, additive concentration, and / or current density in the electrolyte, but this is not a limitation.
[0030] According to embodiments of the present invention, the passivation layer may include a ferromagnetic metal, such as nickel, and thus affect the magnetization intensity of the hysteresis loop of the surface-treated copper foil. The passivation layer may be, for example, a metal layer or a metal alloy layer. The aforementioned metal layer may be selected from, but is not limited to, nickel, zinc, chromium, cobalt, molybdenum, iron, tin, vanadium, tungsten, and titanium. Furthermore, the metal layer and metal alloy layer may be a single-layer or multi-layer structure, such as a zinc-containing and nickel-containing single layer stacked on top of each other.
[0031] A rust-preventive coating is a coating applied to metal to prevent the metal from deteriorating due to corrosion or other factors. The rust-preventive coating may contain a metal or an organic compound, but is not limited to these. When the rust-preventive coating contains a metal, the metal may be chromium or a chromium alloy, and the chromium alloy may further contain a compound selected from nickel, zinc, cobalt, molybdenum, vanadium, and combinations thereof. When the rust-preventive coating contains an organic compound, non-limiting examples of organic molecules that can be used to form the organic rust-preventive coating include porphyrin groups, benzotriazoles, triazine trithiols, and combinations thereof, wherein the porphyrin group is composed of porphyrin, porphyrinic macrocycle, expanded porphyrin, contracted porphyrin, linear porphyrin polymers, porphyrin interlayer coordination complexes, porphyrin arrays, 5,10,15,20-tetra(4-aminophenyl)-porphyrin-zinc(II), and combinations thereof.
[0032] The coupling layer can be made of silane. According to an embodiment of the present invention, the silicon concentration in the first surface treatment layer 112a is mainly contributed by the coupling layer 120 therein. The coupling layer 120 composed of silane can be formed by spraying. During the formation of the coupling layer 120, the alkoxy groups in the silane can be hydrolyzed into hydroxyl groups. These hydroxyl groups can not only form bonds with the attached metal layer, but also undergo condensation polymerization in adjacent silane molecules, thereby changing the adhesion between the silane and the metal layer. In addition, the silane may also include amino groups, epoxy groups, and / or alkylene groups. Therefore, during the subsequent bonding of the surface-treated copper foil to the carrier plate, these functional groups can form bonds with the polymers in the carrier plate, thereby improving the adhesion between the surface-treated copper foil and the carrier plate.
[0033] According to embodiments of the present invention, the silicon concentration in the coupling layer 120 is related not only to the total organic carbon (TOC) content of the adjacent anti-rust layer 118a, but also to the surface morphology or composition of the first passivation layer 116a and / or the main copper foil 110. Without being limited to any theory, it is speculated that, with differences in total organic carbon content and the surface morphology and composition of the adhered layers, the amount of silane adsorbed onto the anti-rust layer 118a during the formation of the coupling layer 120 may be affected, thereby affecting the silicon concentration in the coupling layer 120.
[0034] The silanes mentioned above can be selected from, but are not limited to, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, glycidoxypropyltriethoxysilane, 8-glycidoxyoctyltrimethoxysilane, 3-methacryloyloxypropyltriethoxysilane, 8-methacryloyloxyoctyltrimethoxysilane, 3-acryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, and vinyltriethoxysilane, and are used to improve the adhesion between surface-treated copper foil and other materials (e.g., carriers).
[0035] The aforementioned surface-treated copper foil can be further processed into a copper clad laminate (CCL). The copper clad laminate includes at least a carrier plate and surface-treated copper foil, with the surface-treated copper foil disposed on at least one surface of the carrier plate. The treated surface of the surface-treated copper foil faces and directly contacts the carrier plate.
[0036] The carrier board can be made of bakelite, polymer board, or fiberglass board, but is not limited to these. Examples of polymer components in the polymer board include: epoxy resin, phenolic resin, polyester resin, polyimide resin, acrylic, formaldehyde resin, bismaleimide triazine resin (also known as BT resin), cyanate ester resin, fluoropolymers, polyethersulfone, cellulose thermoplastics, polycarbonate, polyolefins, polypropylene, polysulfides, polyurethane, polyimide resin, liquid crystal polymers, and polyoxymethylene. The fiberglass board can be a prepreg material formed by impregnating fiberglass nonwoven fabric with the aforementioned polymers (such as epoxy resin).
[0037] The aforementioned copper foil substrate can be further processed into a printed circuit board, the steps of which may include patterning the surface-treated copper foil to create wires and bonding two adjacent substrates together.
[0038] The following section provides an illustrative description of the method for fabricating surface-treated copper foil. The steps involved in the fabrication process are described below:
[0039] (1) Step A
[0040] Step A utilizes filtration or ion exchange technology to pretreat the electrolyte used in the electrodeposition process. This pretreatment removes ferromagnetic metal ions from the electrolyte or reduces the ratio of ferromagnetic metal ions to other metal ions. For example, ion exchange technology can be used to pass the electrolyte through a column filled with an ion-exchange polymer. This replaces ferromagnetic metal ions such as iron, nickel, and cobalt ions with non-ferromagnetic sodium or potassium ions, or with hydrogen ions. The ion-exchange polymer can be a chelating resin (Purolite Corporation), and the electrolyte flow rate is 2–7 volumetric flow rate per resin volume (BV / min). The electrolyte can be treated with the ion-exchange resin once or multiple times to achieve a predetermined concentration of ferromagnetic metal ions such as iron, nickel, and cobalt ions in the electrolyte.
[0041] (2) Step B
[0042] Step B utilizes the pre-treated electrolyte to perform an electrodeposition process to form the copper foil body. For example, a foil-making machine can be used to form the copper foil body, also known as raw copper foil, through electrolytic deposition. The foil-making machine may include at least a roller serving as the cathode, a pair of insoluble metal anode plates, and an electrolyte inlet manifold. The roller is a rotatable metal roller with a mirror-polished surface. The metal anode plates are detachably fixed to the lower half of the roller, surrounding it. The inlet manifold is fixed directly below the roller and located between the two metal anode plates.
[0043] During the electrodeposition process, an electrolyte feed pipe continuously supplies electrolyte between the roller and the metal anode plate. By applying current or voltage between the roller and the metal anode plate, copper can be electrodeposited onto the roller to form a copper foil body. Furthermore, by continuously rotating the roller and peeling the copper foil body off the roller, a continuous series of copper foil bodies can be produced. The surface of the copper foil body facing the roller is called the roller surface, while the surface of the copper foil body away from the roller is called the deposition surface.
[0044] The manufacturing parameter ranges for the copper foil body are illustrated below:
[0045] <2.1 Electrolyte Composition and Electrolysis Conditions>
[0046] Copper sulfate (CuSO4·5H2O): 320 g / L
[0047] Sulfuric acid: 95g / L
[0048] Chloride ions (from hydrochloric acid, RCI Labscan Ltd.): 30 mg / L (ppm)
[0049] Gelatin (DV, Nippi, Inc.): 0.35 mg / L (ppm)
[0050] Ferromagnetic metal ions (iron, nickel, cobalt): 503–4011 ppm
[0051] Liquid temperature: 30~65℃
[0052] Current density: 40~80A / dm 2
[0053] Copper foil body thickness: approximately 33μm
[0054] (3) Step C
[0055] Step C involves performing a surface cleaning process on the copper foil body to ensure that the surface of the copper foil body is free of contaminants (such as oil or oxides). The manufacturing parameter ranges are illustrated below:
[0056] <3.1 Composition of the cleaning solution and cleaning conditions>
[0057] Copper sulfate: 200g / L
[0058] Sulfuric acid: 100g / L
[0059] Liquid temperature: 25℃
[0060] Soaking time: 5 seconds
[0061] (4) Step D
[0062] Step D forms a roughening layer on any surface of the copper foil body. For example, roughening particles can be formed on the roller surface of the copper foil body by electrodeposition. Furthermore, to prevent the roughening particles from falling off, a capping layer can be further formed on the roughening particles. Examples of manufacturing parameter ranges for the roughening layer (including the roughening particles and the capping layer) are shown below:
[0063] <4.1 Parameters for creating coarsened particles>
[0064] Copper sulfate (CuSO4·5H2O): 150 g / L
[0065] Sulfuric acid: 100g / L
[0066] Liquid temperature: 25℃
[0067] Current density: 40A / dm 2
[0068] Time: 10 seconds
[0069] <4.2 Parameters for Creating Overlays>
[0070] Copper sulfate (CuSO4·5H2O): 220 g / L
[0071] Sulfuric acid: 100g / L
[0072] Liquid temperature: 40℃
[0073] Current density: 15A / dm 2
[0074] Time: 10 seconds
[0075] (5) Step E
[0076] Step E forms a passivation layer on each side of the copper foil body. For example, an electrodeposition process can be used to form a passivation layer with a double-layer stacked structure (e.g., a nickel-containing layer / zinc-containing layer, but not limited thereto) on the side of the copper foil body where the roughening layer is provided, and a passivation layer with a single-layer structure (e.g., a zinc-containing layer, but not limited thereto) on the side of the copper foil body where the roughening layer is not provided. Examples of manufacturing parameter ranges are shown below:
[0077] <5.1 Electrolyte composition and electrolysis conditions containing nickel layer>
[0078] Nickel sulfate (NiSO4·7H2O): 180 g / L
[0079] Boric acid (H3BO3): 30g / L
[0080] Sodium hypophosphite (NaH2PO2): 3.6 g / L
[0081] pH value: 3.5
[0082] Liquid temperature: 20℃
[0083] Current density: 0.2~0.5A / dm 2
[0084] Time: 10 seconds
[0085] <5.2 Electrolyte composition and electrolysis conditions for zinc-containing layers>
[0086] Zinc sulfate (ZnSO4·7H2O): 9 g / L
[0087] pH value: 13
[0088] Liquid temperature: 20℃
[0089] Current density: 0.2 A / dm 2
[0090] Time: 10 seconds
[0091] (6) Step F
[0092] In step F, a rust-preventive layer, such as a chromium-containing layer, is formed on the passivation layer on each side of the copper foil body. Examples of manufacturing parameter ranges are shown below:
[0093] <6.1 Electrolyte composition and electrolysis conditions for chromium-containing layers>
[0094] Chromium trioxide (CrO3): 5 g / L
[0095] Total organic carbon content: 105–1022 ppm
[0096] Liquid temperature: 30℃
[0097] Current density: 5A / dm 2
[0098] Time: 10 seconds
[0099] (7) Step G
[0100] In step G, a coupling layer is formed on the side of the copper foil body where the coarsening particles, the covering layer, the passivation layer, and the rust-preventing layer are provided. For example, after completing the electrodeposition process described above, the copper foil is washed with water, but the surface of the copper foil is not dried. Then, an aqueous solution containing a silane coupling agent is sprayed onto the rust-preventing layer on the side of the copper foil body where the coarsening particles are provided, allowing the silane coupling agent to adhere to the surface of the rust-preventing layer. Afterward, the treated copper foil body can be placed in an oven to dry. Examples of manufacturing parameter ranges are shown below:
[0101] <7.1 Parameters of Silane Coupling Agents>
[0102] Silane coupling agents (which may include single or multiple siloxane compounds): 3-glycidoxypropyl trimethoxysilane (KBM-403), 3-aminopropyltriethoxysilane (S-330), 3-(methacryloxypropyl)methoxysilane (KBM-503), 3-acryloxypropyltrimethoxysilane (KBM-5130), or vinyltrimethoxysilane (KBM-1003).
[0103] The concentration of silane coupling agent in the aqueous solution is 0.25 wt.%.
[0104] Spraying time: 10 seconds
[0105] To enable those skilled in the art to implement the present invention, the following detailed description of various specific embodiments of the present invention will further illustrate the surface-treated copper foil and copper foil substrate of the present invention. It should be noted that the following embodiments are merely illustrative and should not be construed as limiting the present invention. That is, without departing from the scope of the present invention, the materials used, the amount and ratio of materials, and the processing procedures in each embodiment can be appropriately changed.
[0106] Examples 1-9
[0107] Examples 1-9 are surface-treated copper foils, and their manufacturing processes correspond to steps A to G in the above-described manufacturing method. The manufacturing parameters that differ between Examples 1-9 and the above-described manufacturing method are listed in Table 1. Specifically, for the surface-treated copper foils of Examples 1-9, the following parameters are used: Figure 2The structure shown has a roughening layer on the roller surface, and a nickel-containing layer, a zinc-containing layer, a chromium-containing layer, and a coupling layer are sequentially formed on the roughening layer. On the side of the copper foil body without the roughening layer, a zinc-containing layer and a chromium-containing layer are sequentially formed. The thickness of the surface-treated copper foil is 35 μm.
[0108] Comparative Examples 1-9
[0109] The manufacturing processes of Comparative Examples 1-9 correspond to steps A to G in the above-described manufacturing method. The manufacturing parameters that differ between Comparative Examples 1-9 and the above-described manufacturing method are listed in Table 1. Specifically, the surface-treated copper foil of Comparative Examples 1-9 uses the following... Figure 2 The structure shown has a roughening layer on the roller surface, upon which a nickel-containing layer, a zinc-containing layer, a chromium-containing layer, and a coupling layer are sequentially formed. On the side of the copper foil body without a roughening layer, a zinc-containing layer and a chromium-containing layer are sequentially formed. The thickness of the surface-treated copper foil is 35 μm.
[0110] Table 1
[0111] The following further describes the test results of Examples 1-9 and Comparative Examples 1-9, such as: <magnetization intensity>, <pole height>, <silicon concentration>, <signal transmission loss>, <normal peel strength>, <infrared reflow peel strength>, and <peel strength retention rate>. The test results are recorded in Tables 2 and 3 respectively.
[0112] <Magneticsaturation>
[0113] A superconducting quantum interference device (SQUID) was used to apply a gradually varying external magnetic field to a 5mm × 5mm surface-treated copper foil to measure its hysteresis loop. When the applied magnetic field was zero, the corresponding magnetization intensities in the hysteresis loop were defined as a first magnetization and a second magnetization. The absolute difference between the first and second magnetization intensities, divided by the sample volume, was defined as the magnetization difference. The vector direction of the applied magnetic field was perpendicular to the thickness extension direction of the surface-treated copper foil. Specific measurement conditions are as follows, and the measurement results are recorded in Tables 2 and 3:
[0114] Model: MPMS3
[0115] External magnetic field strength range: 0~10kOe
[0116] The scanning method of the applied magnetic field is as follows: 0kOe → 10kOe → -10kOe → 10kOe
[0117] Measurement interval: 1 kOe
[0118] Air temperature: 25±3℃
[0119] Sample area: 5mm × 5mm
[0120] Sample thickness: Weight per unit area of surface-treated copper foil (g / m²) 2 Divide by the density of copper foil (g / m³) 3 )
[0121] <Pole Height (Sxp)>
[0122] According to standard ISO 25178-2:2012, the extreme point height (Sxp) of the treated surface of the surface-treated copper foil was measured using a laser microscope (LEXT OLS5000-SAF, Olympus). Specific measurement conditions are as follows, and the results are recorded in Tables 2 and 3:
[0123] Light source wavelength: 405nm
[0124] Objective lens magnification: 100x objective lens (MPLAPON-100x LEXT, Olympus)
[0125] Optical zoom: 1.0x
[0126] Observation area: 129μm × 129μm
[0127] Resolution: 1024 pixels × 1024 pixels
[0128] Condition: Automatic tilt removal function of the laser microscope is enabled.
[0129] Filter: No filter
[0130] <Silicon Concentration>
[0131] X-ray photoelectron spectroscopy (XPS) was used to measure the surface-treated copper foil, specifically the surface-treated layer located on one side of the treated surface, to determine the atomic percentage (atomic%) of the silicon concentration in the surface-treated layer. Specific measurement conditions are as follows, and the results are recorded in Table 3:
[0132] Model: VGESCALAB 250, Thermo Fisher
[0133] Anode target material: aluminum
[0134] Light source: Monochrome Al K α Line (1486.9 eV)
[0135] Beam size: 650μm
[0136] Measurement depth: 5–10 nm
[0137] Analyzed elements: Ni, Cu, Zn, Co, Cr, Si, C, N, O, P, S
[0138] Detection conditions: (1) Pass energy = 100 eV; (2) Step size = 1 eV; (3) Rate = 50 ms
[0139] <Signal transmission loss>
[0140] The surface-treated copper foil of any of the above embodiments is made as shown in the example. Figure 3 The stripline 300 is shown, and its corresponding signal transmission loss is measured. Regarding the fabrication method of the stripline 300, a surface-treated copper foil from any of the above embodiments is first bonded onto a 152.4 μm resin (S7439G, Shengyi Technology Co.). Then, the surface-treated copper foil is used to fabricate a conductor 302. Multiple sheets of resin (S7439G, Shengyi Technology) are then used to cover the conductor 302, so that the conductor 302 is disposed within a dielectric 304 (S7439G, Shengyi Technology). The stripline 300 may further include two ground electrodes 306-1 and 306-2, respectively disposed on opposite sides of the dielectric 304. The ground electrodes 306-1 and 306-2 are electrically connected to each other through conductive vias, so that the ground electrodes 306-1 and 306-2 have equipotential. The specifications of each component in the stripline 300 are as follows:
[0141] Length of wire 302: 100mm
[0142] Wire width w: 120μm
[0143] The conductor thickness t is 35 μm.
[0144] Dielectric properties of dielectric 304: Dk = 3.74, Df = 0.006 (measured according to IPC-TM 650 No. 2.5.5.5, with a 10GHz signal).
[0145] Characteristic impedance: 50Ω
[0146] Status: No covering film
[0147] When measuring signal transmission loss, according to the standard Cisco S3 method, a signal analyzer is used with both ground electrodes 306-1 and 306-2 at ground potential. An electrical signal is input from one end of conductor 302, and the output value at the other end of conductor 302 is measured to determine the signal transmission loss generated by the stripline 300. Specific measurement conditions are as follows:
[0148] Signal Analyzer: PNA N5227B (Keysight Technologies)
[0149] Electrical signal frequency: 10MHz to 20GHz
[0150] Scan count: 2000 points
[0151] Calibration method: E-Cal (cal kit: N4692D)
[0152] Using an electrical signal frequency of 16 GHz, the degree of signal transmission loss in the corresponding stripline was determined. A smaller absolute value of the signal transmission loss indicates less signal loss during transmission. The test results are recorded in Table 2. The evaluation criteria are as follows:
[0153] ◎ (Represents optimal signal transmission performance): The absolute value of signal transmission loss is less than 0.75 dB / in.
[0154] ○ (Indicates good signal transmission performance): The absolute value of signal transmission loss is between 0.75 dB / in and 0.8 dB / in.
[0155] X (representing the worst signal transmission performance): The absolute value of the signal transmission loss is greater than 0.8 dB / in.
[0156] <Normal peel strength>
[0157] The treated side of the surface-treated copper foil is placed face down onto the resin (S7439G, Shengyi Technology Co., Ltd.), and the two are pressed together to form a laminate. The pressing conditions are as follows: temperature 200°C, pressure 100 psi, and pressing time 120 minutes.
[0158] Subsequently, according to standard IPC-TM-650 2.4.8, a universal testing machine (AG-I, Shimadzu Corp.) was used to peel the surface-treated copper foil off the laminate at a 90° angle. The measurement results are recorded in Table 2.
[0159] <Infrared Reflow Peel Strength>
[0160] The treated side of the surface-treated copper foil is placed face down onto the resin (S7439G, Shengyi Technology Co., Ltd.), and the two are pressed together to form a laminate. The pressing conditions are as follows: temperature 200°C, pressure 100 psi, and pressing time 120 minutes.
[0161] Next, the laminated board undergoes heat treatment in an infrared reflow oven. The heat treatment conditions are as follows: ambient temperature 260℃, reflow time 60 seconds per cycle, and 10 reflows. After each reflow, the laminated board is cooled to room temperature before the next reflow is performed.
[0162] Next, according to standard IPC-TM-650 2.4.8, a universal testing machine (AG-I, Shimadzu Corp.) was used to peel the surface-treated copper foil off the laminate at a 90° angle. The measurement results are recorded in Tables 2 and 3.
[0163] <Peel strength retention rate>
[0164] For the aforementioned surface-treated copper foil's "normal peel strength" and "infrared reflow peel strength," the "infrared reflow peel strength" is used as the numerator, and the "normal peel strength" is used as the denominator to calculate the corresponding peel strength retention rate (i.e., the value obtained by dividing the "infrared reflow peel strength" by the "normal peel strength"). The closer the peel strength retention rate is to 100%, the better the adhesion of the corresponding surface-treated copper foil. The calculation results are recorded in Table 3.
[0165] Table 2
[0166] Note 1: This indicates a situation where the laminated board delaminates or cracks during the heat treatment process in the infrared reflow oven.
[0167] According to Examples 1-9 described in Table 2, when the pole height (Sxp) of the processed surface is 0.4-2.5 μm, and when the absolute difference between the first magnetization and the second magnetization (i.e., the magnetic field strength difference) is 20-1200 emu / m 3 At that time, the corresponding signal transmission loss was at least at a good level, the corresponding normal peel strength was higher than or equal to 4.53 lb / in, and the corresponding infrared reflow peel strength was higher than or equal to 4.15 lb / in. In contrast, for Comparative Examples 1 to 7, when either the pole height (Sxp) or the magnetic field strength difference did not fall within the above range, even if the signal transmission loss of a specific comparative example (e.g., Comparative Examples 3, 5, and 7) was still at the best level, at least one of its corresponding normal peel strength and infrared reflow peel strength would be inferior to any of those in Examples 1 to 9.
[0168] For Examples 1, 2, 5, 6, and 9, when the absolute difference between the first magnetization and the second magnetization (i.e., the magnetic field strength difference) is 20–800 emu / m 3 Furthermore, by controlling the pole height (Sxp) of the processing surface to 0.4–1.8 μm, the degree of signal transmission loss can be further reduced.
[0169] For Examples 1, 2, 5, and 6, when the pole height (Sxp) of the processed surface is 0.4–2.5 μm, and the absolute difference between the first and second magnetization intensities (i.e., the magnetic field strength difference) is further controlled to be 20–500 emu / m 3 At that time, the corresponding signal transmission loss is at the optimal level.
[0170] Table 3
[0171] According to Examples 1 to 9 described in Table 3, when the pole height (Sxp) of the processed surface is 0.4 to 2.5 μm, and the absolute difference between the first magnetization and the second magnetization (and the magnetization difference) is 20 to 1200 emu / m 3 Furthermore, when the Si concentration of the surface treatment layer is controlled to be 2–15 at%, the corresponding normal peel strength can be higher than or equal to 4.53 lb / in, and the corresponding infrared reflow peel strength can be higher than or equal to 4.15 lb / in. In contrast, for Comparative Examples 3, 5, 8, and 9, when any one of the pole height (Sxp), magnetic field strength difference, and Si concentration does not fall within the above range, at least one of the corresponding normal peel strength and infrared reflow peel strength is inferior to that of the embodiments.
[0172] Furthermore, for Examples 1-4 and 7, when the Si concentration of the surface treatment layer is controlled to be 2.5-11.5 at%, or 2.5-8.0 at%, the peel strength retention rate can be further improved. The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made in accordance with the claims of the present invention shall fall within the protection scope of the present invention.
Claims
1. A surface-treated copper foil, characterized in that, The surface treatment includes a processing surface with a pole height of 0.4–2.5 μm. For the hysteresis loop of the surface-treated copper foil, the hysteresis loop exhibits a first magnetization and a second magnetization when the magnetic field is zero. The absolute difference between the first magnetization and the second magnetization is 20–1200 emu / m. 3 .
2. The surface-treated copper foil as described in claim 1, characterized in that, The pole height of the processed surface is 0.4–1.8 μm, and the absolute difference between the first magnetization and the second magnetization is 20–800 emu / m. 3 .
3. The surface-treated copper foil as described in claim 1, characterized in that, The absolute difference between the first magnetization and the second magnetization is 20–500 emu / m. 3 .
4. The surface-treated copper foil according to any one of claims 1 to 3, characterized in that, Further includes: A copper foil body; and A surface treatment layer is disposed on at least one surface of the copper foil body, wherein the outermost side of the surface treatment layer is the treated surface.
5. The surface-treated copper foil as described in claim 4, characterized in that, When X-ray photoelectron spectroscopy analysis is performed on the treated surface and Ni, Cu, Zn, Co, Cr, Si, C, N, O, P, and S are used as the target atoms for analysis, the total number of the target atoms is used as the calculation basis, and the Si concentration of the surface treatment layer is 2 to 15 at%.
6. The surface-treated copper foil as described in claim 5, characterized in that, The Si concentration of the surface treatment layer is 2.5–11.5 at%.
7. The surface-treated copper foil as described in claim 5, characterized in that, The Si concentration of the surface treatment layer is 2.5–8.0 at%.
8. The surface-treated copper foil as described in claim 4, characterized in that, The surface treatment layer includes at least two sub-layers, and one of the at least two sub-layers is selected from the group consisting of a roughening layer, a passivation layer, and a rust-preventing layer.
9. The surface-treated copper foil as described in claim 8, characterized in that, The other of the at least two sub-layers is a silicon-containing coupling layer.
10. The surface-treated copper foil as described in claim 8, characterized in that, At least one of the roughening layer, the passivation layer, and the rust-preventing layer comprises a ferromagnetic metal.
11. The surface-treated copper foil as described in claim 10, characterized in that, The ferromagnetic metal includes nickel, cobalt, or iron.
12. A copper foil substrate, characterized in that, include: Carrier plate; as well as The surface-treated copper foil as described in claim 1, wherein the treated surface is adhered to the carrier plate.
Citation Information
Patent Citations
Surface-treated copper foil, carrier-attached copper foil, copper-clad laminate, and printed wiring board
CN112969824A
Ceramic wiring board and its production
JP1999251699A